1998
DOI: 10.1046/j.1365-2141.1998.01111.x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of lung‐resistance protein and increased P‐glycoprotein function in acute myeloid leukaemia cells predict a poor response to chemotherapy and reduced patient survival

Abstract: Summary.We investigated the role of the drug resistancerelated proteins LRP, MRP and Pgp and the apoptotic suppressor, bcl-2, in relation to other clinical characteristics, with respect to response and survival in 91 patients with newly diagnosed AML, treated with standard chemotherapy. Multivariate analysis showed that poor response to chemotherapy was associated with increasing age (P ¼ 0·0004), LRP expression (P ¼ 0·0001) and Pgp function (P ¼ 0·015). The significant predictors of both leukaemia-free surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0
3

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 38 publications
6
60
0
3
Order By: Relevance
“…The present univariate results on LRP confirm our initial results in 82 patients, 12 and are consistent with published studies. 11,20,26 List et al 11 reported a significant association between LRP overexpression and both an inferior response to induction chemotherapy and a trend toward shorter survival on, in comparison to our study, a more heterogeneous study Complete remission rates and median overall survival dependent on the number of risk factors (age у60 years, poor karyotype, LRP expression) are shown.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…The present univariate results on LRP confirm our initial results in 82 patients, 12 and are consistent with published studies. 11,20,26 List et al 11 reported a significant association between LRP overexpression and both an inferior response to induction chemotherapy and a trend toward shorter survival on, in comparison to our study, a more heterogeneous study Complete remission rates and median overall survival dependent on the number of risk factors (age у60 years, poor karyotype, LRP expression) are shown.…”
Section: Discussionmentioning
confidence: 84%
“…9,10,20 In a recent study by Marie's group, outcome of induction chemotherapy correlated with MRP function but not with MRP expression. 28 Shorter survival in the presence of bcl-2 expression (Figure 1) has recently also been shown by others.…”
Section: Leukemiamentioning
confidence: 99%
See 2 more Smart Citations
“…There are 49 human genes in the ATP-binding cassette (ABC) transporter superfamily encoding transmembrane proteins, which mediate drug efflux via ATP-dependent pumps (17)(18)(19)(20)(21). Among the ABC transporters, expression of multidrug resistance protein 1 (MDR1 or P-glycoprotein) and breast cancer resistance protein 1 (BCRP1) have been associated with chemotherapy resistance in AML in some studies (22)(23)(24)(25)(26)(27)(28) although not in all (29)(30)(31)(32). One possible reason for the conflicting prognostic relevance suggested for ABC transporter expression in AML is the variety of methods used to assess that expression in previous studies (33).…”
Section: Introductionmentioning
confidence: 99%